ANTIMICROBIAL POTENTIAL OF DENTURE BASE MATERIALS MODIFIED WITH METAL-BASED NANOPARTICLES - Lugova, Liubov; Dobrovolska, Oksana; Dobrovolskyi, Oleksandr; Vazhnichaya, Elena; Sydorenko, Antonina; Bobrova, Nellia (Eastern Ukrainian Medical Journal, 2026)
Introduction. Removable dentures remain a popular type of dental prosthetics and provide significant improvements in oral care and quality of life for edentulous patients. Acrylic resins, especially polymethyl methacrylate, are known materials for the removable dentures, but do not exclude complications of microbial origin in users, which requires their improvement. The aim of the work is to review the current scientific literature on the use of metal/metal oxide nanoparticles (NPs) to impart the antimicrobial properties to acrylic denture base materials Methods. The search for literature was carried out in the PubMed/Medline database. After applying the inclusion and exclusion criteria, 76 documents were selected for final consideration. Results. It was shown that the oral microbiome has certain features in persons with dentures. The denture surfaces are easily colonized by bacteria and fungi, which form a biofilm and become potential pathogens. To prevent this, prosthetic materials are modified with metal/metal oxide NPs. The NP ability to inhibit microorganisms depends on the surface charge, size, shape and coating of NPs, their concentration, nature of the medium, the phase of microorganism development, features of the microbial cell wall, and biofilm formation. Silver NPs are widely used for modification of denture materials. They have a wide range of antibacterial action and antifungal properties, anti-adhesive and antibiofilm activity. The development of surfaces resistant to microbial colonization can also be carried out by incorporating NPs of zinc oxide, titanium dioxide, zirconium dioxide, and copper oxide NPs into the acrylic resin. Conclusions. Therefore, metal/metal oxide NPs can improve the antimicrobial properties of denture base materials, however, clinical “translation” of nanoengineered dentures requires a standardized technology for introducing NPs into/on dentures, achieving local long-term NPs release, and ensuring safety for humans.